Characteristics of Criminal Acts of Corruption in Indonesia - Pabalik, Daeng; Hatta, Muhammad; Hidaya, Nur; Rinaldy Bima, 4Muhammad; Djanggih, Hardianto (International Journal of Psychosocial Rehabilitation, 2020)
Corruption in Indonesia is almost happening throughout the level of government both at the central and regional levels. Although there are various disagreeing parties of corruption classified as extraordinary crimes legal experts generally argue that corruption in Indonesia can be categorized as an extraordinary crime because it is organized, Systemic and has been looting so that it can negatively impact economic growth, legal enforcement and national security stability. Therefore, to tackle corruption crimes in Indonesia, the government has issued law No. 31 of 1999 and No. 20 of 2001 on the eradication of corruption crimes as a legal basis for the eradication of corruption in Indonesia. However, with the issuance of law No. 19 of 2019 for the amendment of law No. 30 of 2002 on the Eradication Commission, various legal experts have assessed that corruption crimes in Indonesia can no longer be classified as crimes Extraordinary because some of the extraordinary powers that KPK has as the spearhead of corruption eradication in Indonesia have been eliminated.